The Role of The Constitutional Court in The Protection of Basic Rights Based on the 1945 Constitution - Ariena Khairunisa Gunawan (Dinasti Research, 2026)
The Constitutional Court is a state institution established with the main function of acting as the guardian of the Constitution. One of the key reasons for its establishment is to protect the fundamental rights guaranteed by the Constitution from interference by the legislative and executive branches. Through the mechanism of judicial review, the Constitutional Court plays a crucial role in maintaining and ensuring that fundamental rights such as freedom of expression, freedom of religion, the right to education, and protection from discrimination are properly implemented and not violated by laws or regulations that contradict the 1945 Constitution. Therefore, it is important to examine the extent to which the Constitutional Court can independently carry out its function of guaranteeing the protection of citizens’ fundamental rights.